A comparative study of three guava varieties (Psidium guajava) for jelly-making. - Estrera, Jasmin T.
Jellies were prepared from the three guava varieties, commonly named Pakistan, Peru and Vietnam guavas to determine which of the three varieties would yield the most acceptable jelly., The three guava varieties were also evaluated according to pectin content, total titrable acidity, reducing sugar content and moisture content. Results showed that Peru guava is highest in pectin content. Pakistan guava is highest in moisture content and total titrable acidity. In terms of reducing sugar content, Peru guava is higher than Vietnam guava. The jellies were evaluated according to their sensory attributes by conducting a sensory evaluation test using a descriptive score card. Acceptability was determined by using a 9-point hedonic scale. Results showed that there is a significant difference in appearance, color and consistency in all three varieties. Peru guava, having the highest pectin content, yielded the most viscous jelly. No significant difference is observed in the flavor of the three varieties. As to general acceptability, no significant difference is observed at a 5 level, and all samples rated "moderately acceptable".